2007
DOI: 10.2174/092986707780597998
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Transcription by PARP-1: Consequences in Carcinogenesis and Inflammation

Abstract: Post-translational modification of proteins by poly(ADP-ribosyl)ation is involved in the regulation of a number of biological functions. While an 18 member superfamily of poly(ADP-ribose) polymerases (PARP)s has been described PARP-1 accounts for more than 90% of the poly(ADP-ribosyl)ating capacity of the cells. PARP-1 act as a DNA nick sensor and is activated by DNA breaks to cleave NAD(+) into nicotinamide and ADP-ribose to synthesize long branching poly(ADP-ribose) polymers (PAR) covalently attached to nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 85 publications
(133 reference statements)
1
81
0
Order By: Relevance
“…Our gene expression analysis in the hippocampus after OR training demonstrated the increase in NF-B and CREB gene targets and, in both cases, training-induced NF-B-and CREB-dependent gene expression required of PARP-1 activation. It is well known that PARP-1 works as a coactivator of NF-B in some cell types (Aguilar-Quesada et al, 2007), although to our knowledge this is the first description of PARP-1 and CREB transcriptional cooperation.…”
Section: Discussionmentioning
confidence: 78%
“…Our gene expression analysis in the hippocampus after OR training demonstrated the increase in NF-B and CREB gene targets and, in both cases, training-induced NF-B-and CREB-dependent gene expression required of PARP-1 activation. It is well known that PARP-1 works as a coactivator of NF-B in some cell types (Aguilar-Quesada et al, 2007), although to our knowledge this is the first description of PARP-1 and CREB transcriptional cooperation.…”
Section: Discussionmentioning
confidence: 78%
“…Involvement of PARP-1 on Snail1 activation and E-cadherin expression Previous results have shown that PARP-1 is implicated in the regulation of transcription at different levels (Kim et al, 2005), and its ability to modulate transcription factors involved in tumor development and angiogenesis has been repeatedly reported (Aguilar-Quesada et al, 2007). In the present study, we have analyzed the involvement of PARP-1 and its activity on the modulation of Snail1, a key transcription factor involved in cell migration during development and metastasis.…”
Section: Resultsmentioning
confidence: 88%
“…As pArp-1 actively participates in DnA repair, pArp-1 inhibitors have been applied in cancer treatment either alone or in combination with DnA-damaging agents (14). several studies have demonstrated that pharmacological inhibition or genetic ablation of pArp-1 not only provided remarkable protection from tissue injury in various oxidative stress-related disease models but also resulted in a clear beneficial outcome in the treatment of cancer (15). In certain types of tumors including lung cancer, colon carcinoma and cervical cancer, pArp-1 inhibition was shown to be an effective means of enhancing tumor sensitivity to radiation and chemotherapy (16)(17)(18)(19), also pArp inhibitor could be used as single agents to selectively kill cancers defective in DnA repair, specifically cancers with mutations in the breast cancerassociated genes (BrcA1 and BrcA2) (20,21).…”
Section: Introductionmentioning
confidence: 99%